System Boundaries, Data Sources and Assessment Methods in the Ecological Evaluation of Complex Assembly Products - Funk, Felix; Franke, Jörg (Sustainable Manufacturing as a Driver for Growth. Proceedings of the 19th Global Conference on Sustainable Manufacturing, December 4–6, 2023, Buenos Aires, Argentina, 2025)
Life Cycle Assessment (LCA) has become the most popular method for assessing the environmental impact of products. It is internationally standardized by ISO 14040 and ISO 14044, which outline the general methodology, steps, and issues to be considered. While the standards ensure a consistent general understanding of the method, it does not provide explicit recommendations on the decisions to be made when conducting an LCA. These decisions include, in particular, the definition of system boundaries, the prioritization of data sources, and the selection of appropriate assessment methods. For some industries, particularly raw materials and process goods, the gap has mostly been filled by industry standards. The vast number of manufactured goods that are the result of complex assemblies originating from multi-tiered supply chains still lack such industry standards. This work addresses the issue by conducting a thorough literature review on the subject. As a result of the literature review, methodological gaps are identified and quasi-standards are derived from previous studies, thus providing general guidance for future LCA of complex assembly products.
CRIS-Team Scopus Importer:2025-02-28